ANALISIS FAKTOR GAYA KEPEMIMPINAN DAN FAKTOR ETOS KERJA TERHADAP KINERJA PEGAWAI PADA ORGANISASI YANG TELAH MENERAPKAN SNI 19-9001-2001 - Biatna Dulbert Tampubolon (JURNAL STANDARDISASI, 2007)
An organization which has applied SNI 19-9001-2001, Quality Management System - Requirement, implicitly its officer performance must be good also. If the officer performance almost in entire unit relatively is not yet is maximal, so this research aim to know what factor that influencing the officer performance Leadership style, ethos and officer performance elaborate 30 questions on questionnaire and distributed to 50 officers at random. Then the answers of questionnaire analyses using partial and simultaneous analyst. The research result indicate that leadership style strongly influence the officer performance (Rho=0,811), while ethos less influence toward performance (Rho=0,222). Leadership style and ethos simultaneous analysis is more and more strong influence officer performance (Rho=0,812)